MALAYSIAN INNOVATION ECOSYSTEM: A REVIEW OF THE LITERATURE - Sulaiman, M.Y.; Abdullah, A.; Othman, N.A. (Journal of Advanced Manufacturing Technology (JAMT), 2014)
The capability to innovate and to bring innovation successfully to the market will be a crucial determinant of the global competitiveness of nations over the next decade. Knowing the importance, Malaysia has started to prioritise its national agenda by embedding innovation as one of the major theme of its national economic model. Building a sustainable and supportive ecosystem is one of the keys to ensure an efficient growth strategy. By succeeding in building the sustainable self-reliant innovative system needed, the country aims to become a fully developed nation strategically positioned in the regional and global economic landscape. This paper provides a review of the literature on current status of Malaysian innovation eco-system. The paper concludes that innovation eco-system is essential to nurture innovation in organisation.